Determination of anionic surfactants in sea sand using a multicommutation approach - Ródenas Torralba, Eva; Morales Rubio, íngel; Freire dos Reis, Boaventura; de la Guardia, Miguel (Ciencia, 1970)
It has been employed a mechanized procedure for the spectrophotometric determination of anionic surfactants in sea sand samples. The method is based on a batch leaching of surfactants from sand with two hot water successive treatments followed by on-line reaction of the extracted surfactants with methylene blue (MB) and extraction in chloroform using the multicommutation approach. The dynamic linear range was evaluated till 8.7 í— 10”“6 mol L”“1 (2.48 mg L”“1) sodium dodecyl sulphate (SDS). A solvent consumption of 0.7 mL per determination, a sampling throughput of 40 measurements per hour, a relative standard deviation of 4.2% (n=10) for a 2 í— 10”“6 mol L”“1 (576 Âµg L”“1) surfactant standard and a limit of detection of 1.4 í— 10”“7 mol L”“1 (0.04 mg L”“1) were the analytical parameters obtained for the on-line reaction. Quantitative recoveries, between 92.2 and 100.0%, were found for the determination of anionic surfactants in sand samples spiked with amounts of SDS from 0.75 to 3 Âµg g”“1.